2016
DOI: 10.1002/cssc.201501510
|View full text |Cite
|
Sign up to set email alerts
|

High‐Efficiency Perovskite Solar Cells Employing a S,N‐Heteropentacene‐based D–A Hole‐Transport Material

Abstract: We developed a new donor-π-acceptor-type hole-transport material (HTMs) incorporating S,N-heteropentacene as π-spacer, triarylamine as donor, and dicyanovinylene as acceptor. In addition to appropriate frontier molecular orbital energies, the new HTM showed high photo absorptivity in the visible region. Without the use of p-dopants, solution-processed mixed perovskite devices using the HTM achieved power conversion efficiencies of up to 16.9% and high photocurrents of up to 22.2 mA cm(-2). These results demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
40
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 41 publications
0
40
0
Order By: Relevance
“…On the other hand, the hole-transport materials (HTMs), which separate photo-excited electron-hole pairs and transport the holes to the external circuit, represent another important factor determining device performance. 27 Among various promising HTMs so far reported, 28 the triarylamine-based 2,2',7,7'-tetrakis(N,N-di-pmethoxyphenylamine)-9,9'-spiro-bifluorene (spiro-OMeTAD) is the most effective one. 29 However, the tedious synthesis and purification steps make it expensive for large-scale application.…”
mentioning
confidence: 99%
“…On the other hand, the hole-transport materials (HTMs), which separate photo-excited electron-hole pairs and transport the holes to the external circuit, represent another important factor determining device performance. 27 Among various promising HTMs so far reported, 28 the triarylamine-based 2,2',7,7'-tetrakis(N,N-di-pmethoxyphenylamine)-9,9'-spiro-bifluorene (spiro-OMeTAD) is the most effective one. 29 However, the tedious synthesis and purification steps make it expensive for large-scale application.…”
mentioning
confidence: 99%
“…On the other hand, Bi et al reported a novel D-π-A molecular HSM [32] (15) incorporating S,N-heteropentacene as π spacer, triarylamin as donor, and dicyanovinylene as acceptor. PSCs using 15 achieved similar excellent PCEs of up to 16.9% [53]. However, a much prominent J-V hysteresis phenomenon was observed possibility due to the asymmetric electronic structure of the HSM.…”
Section: Molecular Hsmsmentioning
confidence: 71%
“…Nazeeruddin et al synthesized a series of star‐shaped D‐π‐A molecules as sensitive‐dopant‐free HTMs for PSCs, combining with a elaborative perovskite material as LHM, the PSCs exhibit PCEs of up to 18%. However, most of the D‐A type sensitive‐dopant‐free HTMs reported to date still required multistep synthesis, which limited their potential large‐scale applications in future due to the raised costs . The other is the optimization of high‐efficient doped HTMs in literatures into sensitive‐dopant‐free HTMs.…”
Section: Introductionmentioning
confidence: 99%